PERANAN SYAMSU BAHRUN DALAM MEMPERTAHANKAN KEMERDEKAAN INDONESIA DI PROVINSI JAMBI 1945-1949 - Intan, Devina; Hariadi, Ujang (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2022)
The proclamation of Indonesian independence on August 17, 1945 by Sukarno-Hatta on behalf of the Indonesian people. So, since then Indonesia has become an independent and sovereign country. However, Indonesia's independence was not recognized by the Dutch who considered it a rebellion. The Indonesian people who have felt the suffering and torture by the colonizers do not want it to happen again. The spirit of the struggle to maintain independence was carried out in various regions, including by the people of Jambi who also came forward to participate and take part in actively fighting against the efforts made by the invaders. One of the influential figures in the Jambi area was Syamsu Bahrun, a fighter from the Sarolangun area. Born in 1905 in Pangidaran Village, Pauh District, Sarolangun Regency. Syamsu Bahrun is a figure who is able to give encouragement in defending independence. Syamsu Bahrun is a fighter who is steadfast in principles and beliefs, always putting the interests of the community and nation above his personal interests. Syamsu Bahrun's goal is to realize Indonesia as a sovereign and independent nation. Syamsu Bahrun is a firm person, he is a figure of a freedom fighter who really loves the Jambi Region.